Influence of artificial intelligence tool perceptions on mathematics undergraduates' academic engagement: role of attitudes and usage intentions - Falebita, Oluwanife Segun; Ayanwoye, Olubunmi Kayode; Akinola , Lukman Shina (Universitas Terbuka, 2025)
In African higher education, particularly among STEM students, the rapid integration of Artificial Intelligence (AI) into teaching and learning has created both opportunities for innovation and concerns about ethical use, however, there remains scarce studies about how students perceive and use these technologies in ways that influence their academic engagement and learning outcomes in Mathematics. This study, which focuses on attitudes and usage intentions, seeks to investigate the Influence of AI Tool Perceptions on the academic engagement of mathematics undergraduates from the lens of Technology Acceptance Model (TAM). The Structural Equation Modelling (SEM) approach was used to examine the perceptions of Mathematics undergraduates regarding AI usage and academic engagement. Data collected from 1,518 Mathematics undergraduates from Southwest Nigerian universities through a survey hosted online was analysed using PLS-SEM. The findings indicate that perceptions (perceived ease of use and perceived usefulness) influence attitudes towards and intentions to use AI tools while intention (β = -0.179, t = 2.426, p < 0.05), attitude towards (β = 0.216, t = 2.541, p < 0.05), and actual use of AI (β = 0.797, t = 11.904, p < 0.05) influences academic engagement, intention. According to this study, improving the mathematics students’ perceptions towards the use of AI tools could result in more engaging learning experiences. It highlights the necessity of developing positive attitudes and perceptions to foster academic engagement among undergraduate students in Mathematics programs, as well as the importance of developing supportive learning systems, and institutional regulations that support ethical and effective ways of incorporating AI.